Real Estate Ads on Facebook and Their Impact on the Shift Towards Online Advertising and Purchase Decisions - Wajdi Ali Abdel Salam Abdel Qader; Walid Faraj Muftah Al-Mazoughi (Journal of Scientific and Human Dimensions, 2026)
This study aimed to measure the impact of advertising on social media networks (Facebook) on the trend towards online advertising and purchasing decisions in the Libyan real estate investment market, and to identify the advantages that online advertising on social media networks (Facebook) offers in influencing real estate buyers’ decisions. The descriptive-analytical method was used in this research. A cross-sectional sample of 25 real estate advertising sites on Facebook was selected. The study reached several conclusions, most notably that advertising on social media networks (Facebook) positively influences the trend towards online advertising and that Facebook has a positive impact on purchasing decisions in the real estate sector. The study also showed that online advertising on social media networks (Facebook) achieves marketing advantages and that Facebook ads contribute positively to attracting many real estate buyers. The study recommends the necessity of using scientific methods for advertising on social media platforms and leveraging them to build good relationships with customers, utilizing all other social media channels, and taking advantage of the benefits of advertising on Facebook for advertising and promoting goods and services, given the opportunities this platform offers in Libya compared to other social media channels.